Integrated underground mining and pre-concentration systems; a critical review of technical concepts and developments. Issue 3 (16th March 2021) - Sotoudeh, Farzad; Nehring, Micah; Kizil, Mehmet; Knights, Peter
ABSTRACT: The mining industry is increasingly facing lower feed grades, which is resulting in the necessity to reduce mining and processing costs. One of the most renowned approaches to increasing feed grades is the application of pre-concentration technologies prior to introducing the extracted ore to the main processing plant. This paper reviews the concept of pre-concentration systems and identifies the benefits of pre-concentration in underground mining through the rejection and appropriate deposal of waste and/or low-grade materials. All previous studies into underground pre-concentration theories and applications together with the highlights that were achieved are presented. This is followed by recommendations for future works.